A study on solid waste composition and waste generation rate at Perumahan Indera Mahkota 1 & 2, Kuantan, Pahang - Salihah, Mohamad (2014)
Solid waste is one of the three major environmental problems in Malaysia. It plays a significant role in the ability of nature to sustain life within its capacity. Currently, over 23,000 ton of waste is produced each day in Malaysia. However, this amount is expected to rise to 30,000 ton by the year 2020. A study on solid waste composition and waste generation rate at perumahan Indera Mahkota 1 & 2, Kuantan, Pahang are conducted at 20 sample which where at Taman Kota Ria and Taman Medan Masyhur. Two method are use to determine the solid waste composition, to esimate the waste generation rate in the study area and to study the factor effecting waste generation rate. The method use are by data collection(segrigate and weghing) and questionnaire distribution in a month. The data recorded based on type of house which is single storey and doube storey houses consist of six type of solid waste(food waste, plastic, paper, glass, aluminum and others waste). From the results, it is observed the highest composition of solid waste on both type of house is food waste where 51.83% for Taman Kota Ria(double storey houses) and 57.57% for Taman Medan Masyhur (single storey houses). For the other rest solid waste composition is 15.73%, 10.42%, 9.03%, 6.96%, 6.03% for Taman Kota Ria and 14.29%, 13.16%, 5.8%, 5.07% and 4.11% (Taman Medan Masyhur) for plastic, paper, glass, aluminum, and others waste respectively. The generation rate of MSW recorded are 0.22kg and 0.27kg person 'day' for Taman Kota Ria and Taman Medan Masyhur respectively. From the result, the most factor increasing of solid waste in study area is life style which is consist of household size, income, occupant, education of residential. Beside that, other factor is level of awareness and solid waste management also can be influence the generation rate in residential area.